Efektivitas Penggunaan Proyektor Infocus Pada Pembelajaran Tematik Terhadap Hasil Belajar Siswa - Habibullah, Makmur; Hendrizal, Hendrizal; Amris, Firda Khairati; Ariani, Farida; Wandi, Joni Indra (Institut Agama Islam Sumatera Barat, 2023)
This study aimed to investigate the effectiveness of utilizing an Infocus projector in thematic learning to enhance the academic performance of third-grade students in an elementary school. The research was conducted at State Elementary School 01 2x11 in Kayutanam, Padang Pariaman Regency. The Infocus projector served as a supplementary tool to facilitate a more interactive visualization of the instructional material. A quantitative method with quasi-experimental approach was employed, comparing control group pre-test post-test results within the same classroom. The study's participants comprised 18 third-grade students who had previously undergone traditional instruction without the use of the Infocus projector, and later experienced lessons with the technology. Data regarding students' academic performance were collected through pre- and post-treatment assessments, with statistical tests being employed for data analysis. The inferential analysis revealed a significant difference, with a calculated t-value of 4.58, surpassing the critical t-table value of 1.73. This outcome demonstrated the effectiveness of the Infocus projector in improving student learning outcomes. Notable improvements in student performance were evident when comparing pre-test and post-test results. The descriptive analysis indicated a pre-test score of 41.11 and a post-test score of 77.5. In conclusion, the incorporation of the Infocus projector in thematic instruction had a substantial positive impact on student academic achievement. The findings underscored the educational potential of such technology, emphasizing its importance in creating more engaging and effective learning experiences for elementary school students.